Encapsulating an acid-activatable phthalocyanine–doxorubicin conjugate and the hypoxia-sensitive tirapazamine in polymeric micelles for multimodal cancer therapy. (1st June 2021) - Guo, Xuejiao; Jin, Honglin; Lo, Pui-Chi
Abstract : A multicomponent nanodrug based on polymeric micelles has been fabricated and examined for its potential in combined photodynamic therapy, chemotherapy and hypoxia-activated therapy of cancer. Abstract : A zinc(ii ) phthalocyanine (ZnPc) was conjugated to doxorubicin (Dox) via an acid-labile hydrazone linker. The resulting ZnPc–Dox conjugate was then encapsulated into polymeric micelles formed through self-assembly of a block copolymer of poly(ethylene glycol) and poly(d, l -lactide) both in the absence and presence of the hypoxia-activated prodrug tirapazamine (TPZ) to give ZnPc–Dox@micelles and ZnPc–Dox/TPZ@micelles respectively. These polymeric micelles exhibited an excellent stability in aqueous media, but underwent disassembly in an acidic environment. Upon internalisation into HT29 human colorectal carcinoma cells, fluorescence due to ZnPc and Dox could be observed in the cytoplasm and nucleus respectively for both nanosystems. This observation suggested the disassembly of the polymeric micelles and the cleavage of the hydrazone linker in ZnPc–Dox in the acidic intracellular compartments. These micelles were slightly cytotoxic against HT29 cells in the dark due to the chemotherapeutic effect of Dox and/or TPZ. Upon light irradiation, ZnPc–Dox@micelles showed higher cytotoxicity. The IC50 value under a normoxic condition (0.35 μM based on ZnPc–Dox) was significantly lower than that under hypoxia (>1 μM). With an additional therapeutic component, ZnPc–Dox/TPZ@micelles exhibited higher photocytotoxicity with IC50 values of 0.20 μM and 0.78 μM under normoxia and hypoxia respectively. It is believed that the photodynamic action of this nanosystem consumed the intracellular oxygen and hence triggered the hypoxia-mediated chemotherapeutic action of TPZ. The multimodal antitumor effects of these polymeric micelles were also validated on HT29 tumour-bearing nude mice.